2019
DOI: 10.1097/md.0000000000017866
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-8 gene −251 A/T polymorphism and the risk of coronary artery disease

Abstract: Background: The association between interleukin-8 (IL-8) gene polymorphism −251 A>T and susceptibility to coronary artery disease (CAD) has been investigated previously; however, results remain controversial. Thus, a meta-analysis was conducted to reassess the effects of this polymorphism on CAD risks. Methods: The PubMed, Cochrane Library, China National Knowledge Infrastructure, and Wanfang databases were searched for relevant studies published up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…In this context, increased TLR2 on epithelial cells stimulates the secretion of the cytokines such as IL-6 and IL-8. A connection between high levels of IL-6 and cardiovascular disease ( Qu et al, 2014 ), as well as an association between IL-8 and high risk of coronary artery disease ( Zhang et al, 2019a , b ) have also been reported.…”
Section: Maternal Stress Exposure: Contribution Of Glucocorticoids An...mentioning
confidence: 94%
“…In this context, increased TLR2 on epithelial cells stimulates the secretion of the cytokines such as IL-6 and IL-8. A connection between high levels of IL-6 and cardiovascular disease ( Qu et al, 2014 ), as well as an association between IL-8 and high risk of coronary artery disease ( Zhang et al, 2019a , b ) have also been reported.…”
Section: Maternal Stress Exposure: Contribution Of Glucocorticoids An...mentioning
confidence: 94%
“…IL- Babusikova y col 23 You y col 24 Popko y col 26 Fang y col 27 Moleres y col 28 Wu y col 29 Hu y col 30 Avendaño y col 31 Ulhaq y col 32 −572 G/C Artritis reumatoide Glaucoma primario de ángulo abierto You y col 24 Wu y col 29 -1363 T/G Glaucoma primario de ángulo abierto Wu y col 29 IL-8 -251 A/T Cáncer Cáncer de mama en mujeres iraníes Enfermedad coronaria arteriosclerótica Periodontitis Infección por Clostridium difficile Liua y col 34 Kamali-Sarvestani y col 35 Zhang y col 37 Yang y col 38 Garey y col 39 +781 C/T Carcinoma hepatocelular en población taiwanesa Púrpura de Henoch-Schönlein Osteoartritis Asma bronquial Enfermedad de graves Degeneración macular…”
Section: Origen Celular Funciónunclassified
“…En el metaanálisis desarrollado por Zhang y colaboradores se evaluaron los efectos del SNV -251A/T y el riesgo de sufrir una enfermedad coronaria arteriosclerótica en habitantes de China y se encontró que las personas portadoras del alelo -251A pueden tener un mayor riesgo de desarrollar la enfermedad. 34 En el mismo metaanálisis también se encontró asociación positiva del SNV-251T/A con la periodontitis 35 y con la predisposición a la infección por Clostridium difficile. 36 Variaciones en el gen de la IL-8 se han relacionado además con el desarrollo de enfermedades autoinmunes y degenerativas.…”
Section: Variantes En El Gen De La Il-8unclassified
“…The CAD has been confirmed through the epidemiological studies as multigene cum multifactorial regulated human disease ( Fan et al, 2020 ). The estimated mortality rate will be about 23 million by 2030 ( Zhang et al, 2019 ). Nine million deaths have been recorded in all ages of subjects with CAD and known to be the one of the cause of mortality global-wide ( Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%